2013
DOI: 10.1242/jeb.073635
|View full text |Cite
|
Sign up to set email alerts
|

Influence of latentToxoplasmainfection on human personality, physiology and morphology: pros and cons of theToxoplasma–human model in studying the manipulation hypothesis

Abstract: Toxoplasma as the model organism for studying the parasite manipulation hypothesisToxoplasma gondii is a parasitic protozoan whose effects on human behaviour, personality and other phenotypic traits have been studied most thoroughly, often in the context of the manipulation theory, the theory suggesting that many parasites change the phenotype of their host to increase their chances of transmission to a new host by, for example, predation. There are various reasons why this particular protozoon has become a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(179 citation statements)
references
References 66 publications
3
170
1
5
Order By: Relevance
“…The parasite cannot achieve sexual reproduction in rodents and the described alterations increase the chances of transmission to its final, feline host. T. gondii can also infect other mammals (Poirotte et al, 2016) and is considered to be one of the most frequent infections in humans (Flegr, 2013b;Worth et al, 2013). Behavioral alterations that have been associated with latent toxoplasmosis include multiple forms of schizophrenia, personality disorder, Parkinson disease and Alzheimer disease, as well as increased aggressiveness, decreased willingness to follow social rules, and slower reaction times in men (Flegr, 2013a).…”
Section: Zombie Ants Fearless Rats and Other Prominent Cases Of Manmentioning
confidence: 99%
See 2 more Smart Citations
“…The parasite cannot achieve sexual reproduction in rodents and the described alterations increase the chances of transmission to its final, feline host. T. gondii can also infect other mammals (Poirotte et al, 2016) and is considered to be one of the most frequent infections in humans (Flegr, 2013b;Worth et al, 2013). Behavioral alterations that have been associated with latent toxoplasmosis include multiple forms of schizophrenia, personality disorder, Parkinson disease and Alzheimer disease, as well as increased aggressiveness, decreased willingness to follow social rules, and slower reaction times in men (Flegr, 2013a).…”
Section: Zombie Ants Fearless Rats and Other Prominent Cases Of Manmentioning
confidence: 99%
“…Therefore, the absence of sickness behavior or a lack of any discrimination against parasitized mates (Hari Dass et al, 2011;Adamo, 2014;Adamo et al, 2014) have been suggested as examples of successful host manipulation (Table 2). Second, there is clear evidence that men and women, or male and female rodents, behave differently when suffering from latent toxoplasmosis (Flegr, 2013b). Sexspecific or ontogenetic differences in the responses of hosts to certain parasites are likely to be common, and host manipulation is likely to be routinely overlooked in studies that compare parasitized and non-parasitized individuals at the population level without considering individual parameters such as sex, ontogenetic stage or nutritional status.…”
Section: Searching For General Patterns In Reports On Host Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no association was reported to link anti-Toxoplasma IgG antibody and obesity in 985 individuals examined from Iceland, Sweden and Estonia [16]. In contrast, excessive gestational weight gain was reported during pregnancy in infected women with Toxoplasma compared with uninfected pregnant women [17,18]. In addition, excess weight gain was detected in a murine pregnancy model that mimics toxoplasmosis complications in humans [19].…”
Section: Introductionmentioning
confidence: 99%
“…Infection is mostly self-limiting with no or subtle symptoms, yet can cause severe disease and disorders in infants, when infected during pregnancy, and also in immunocompromised individuals (3,4). The parasite stays dormant for a long time in form of tissue cysts and causes no symptoms (5), yet some authors believe that it causes some personality changes at this stage (6,7).…”
Section: Introductionmentioning
confidence: 99%